2018
DOI: 10.12681/jhvms.15859
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and antimicrobial susceptibility of Salmonella, Listeria, and Campylobacter spp. in raw “souvlaki” marketed in Thessaloniki (Northern Greece)

Abstract: ABSTRACT. Souvlaki is a popular Greek meat product consisting of small chunks or cubes of pork threaded on a small wooden or metal skewer. In the present study, 105 samples of raw pork souvlaki obtained from retail shops in Thessaloniki (Northern Greece) were screened for the incidence of Salmonella, Listeria, and Campylobacter and their susceptibility to various antimicrobial agents; serotyping of the isolates was also performed. Of the samples tested, 1.9% were positive for Salmonella and yielded 3 serovars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…C. jejuni is usually detected in fresh meats, such as chicken, duck, turkey, beef, and pork (Hussain et al, 2007; Korsak et al, 2015; Lee et al, 2017; Narvaez-Bravo et al, 2017; Zhao et al, 2001). Soultos et al (2015) also showed that there was no C. jejuni in 105 Greek meat products, called as souvlaki. Additionally, meat products (pork chops, fermented sausage, and beef/chicken wieners) were negative for C. jejuni (Bohaychuk et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. jejuni is usually detected in fresh meats, such as chicken, duck, turkey, beef, and pork (Hussain et al, 2007; Korsak et al, 2015; Lee et al, 2017; Narvaez-Bravo et al, 2017; Zhao et al, 2001). Soultos et al (2015) also showed that there was no C. jejuni in 105 Greek meat products, called as souvlaki. Additionally, meat products (pork chops, fermented sausage, and beef/chicken wieners) were negative for C. jejuni (Bohaychuk et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These previous studies suggest that C. jejuni does not usually exist in processed meat products, which is consistent with our data. To preserve the food, some hurdles (oxygen, water activity, and other competing bacteria) are involved, and C. jejuni is sensitive to the hurdles (Duffy et al, 2001; Leistner, 2000; Soultos et al., 2015; Zhao et al, 2001). Thus, C. jejuni might not be detected in ground meat products.…”
Section: Resultsmentioning
confidence: 99%